A novel gelcasting induction method for YAG transparent ceramic. Issue 3 (1st February 2021) - Yao, Qing; Zhang, Le; Chen, Hao; Gao, Pan; Shao, Cen; Xi, Xiaoqian; Lin, Ling; Li, Haiyan; Chen, Yanyun; Chen, Linfei
Abstract: Yttrium aluminum garnet (YAG) transparent ceramics are an attractive material for solid-state laser, optical and high temperature structural applications because of their prominent advantages. However, it is difficult to achieve the high-quality ceramics by acrylamide (AM) aqueous gelcasting due to the inhomogeneous of gel body induced by traditional methods of "catalyst + initiator" or "initiator + heating". In this work, a series of gel induction contrast experiments were designed to explore a novel gelcasting induction method. With different gelation process, the SEM of surfaces and fracture surfaces and as-fabricated ceramics quality, it was found the effectiveness of the novel gel induction method "vacuum defoaming + initiator". The method had the ability to improve the uniformity of the gel body by regulating the form of energy injection and having enough time for the stirring of initiator. In addition, the decreasing residual organics would result in contributing to the subsequent debinding and ceramic quality improvement. Therefore, the "vacuum defoaming + initiator" was regarded as an effective induction method to eliminate defect and to achieve the in-line transmittance of as-fabricated YAG ceramic with excellent optical quality at 1064 nm reached 82.8%. This work greatly promotes the application of gelcasting in YAG transparent ceramics.